2007
DOI: 10.1007/s00468-007-0124-4
|View full text |Cite
|
Sign up to set email alerts
|

Spectral composition of photosynthetically active radiation penetrating into a Norway spruce canopy: the opposite dynamics of the blue/red spectral ratio during clear and overcast days

Abstract: The spectral composition of photosynthetically active radiation (PAR) during clear and overcast days was studied above the canopy (U) and at two layers of a dense Norway spruce stand [Picea abies (L.) Karst.] characterized with an average LAI = 7.3 ± 0.8 (middle layer: M) and 12.3 ± 0.7 (lower layer: L). Whereas the spectral composition of PAR incoming on the canopy surface during cloudy days (characterized by diffuse index DI > 0.7) was almost independent of the solar elevation angle, the proportion of the bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…However, the quality of radiation, including its spectral composition within the canopy layer, is also important as it may influence physiology and the photosynthetic apparatus (Navrátil et al 2007;Grant 1997). However, understanding whole plant photosynthesis is complicated due to the pronounced spatial PAR differences (Meir et al 2002).…”
Section: Determination Of Vegetation By Stand Ie Canopy Effectsmentioning
confidence: 99%
“…However, the quality of radiation, including its spectral composition within the canopy layer, is also important as it may influence physiology and the photosynthetic apparatus (Navrátil et al 2007;Grant 1997). However, understanding whole plant photosynthesis is complicated due to the pronounced spatial PAR differences (Meir et al 2002).…”
Section: Determination Of Vegetation By Stand Ie Canopy Effectsmentioning
confidence: 99%
“…Therefore, transmitted diffuse radiation in the understory is characterized by reduced R/FR (≈ 0.15) and B/R (≈ 0.35) ratios compared with that above the canopy (Frankland 1986, Campbell andNorman 1998). However, Navrátil et al (2007) reported that direct solar radiation penetrating into the lower parts of coniferous canopies may have an increased B/R ratio up to 2.5, especially at low solar elevation angles (10-20°).…”
Section: Introductionmentioning
confidence: 94%
“…Plants in natural environments are exposed to incident radiation of varying photon flux density (PFD) and spectral quality (Frankland 1986, Grant 1997, Murchie and Horton 1997, over a wide range of temporal and particularly at low (10-20°) solar elevation angles (Navrátil et al 2007, Urban et al 2007a. Thus, the ratio between the blue (B; 400-500 nm) and red (R; 600-700 nm) spectral regions (B/R) varies from ≈ 0.5 (direct radiation) to ≈ 0.95 (diffuse solar radiation).…”
Section: Introductionmentioning
confidence: 99%
“…Urban et al (2007Urban et al ( , 2012 hypothesised that optimal photosynthetic activity of the canopy is achieved under diffuse radiation (cloudy) conditions, when scattered light penetrates throughout the canopy, illuminating all the leaves to some extent and providing a more uniform distribution of light between the leaves. However, the spectral properties of the diffuse component inside the canopy have only been investigated in a Norway spruce (Picea abies L. Karst)-European beech (Fagus sylvatica L.) forest stand in Southern Germany (Leuchner et al, 2007;Hertel et al, 2011) and a Norway spruce stand by Navrátil et al (2007) and Urban et al (2007Urban et al ( , 2012 in the Czech Republic. No measurements are known from higher latitudes.…”
Section: Introductionmentioning
confidence: 99%